PENGEMBANGAN DAN VALIDASI METODE PENENTUAN KADAR ANTRAKUINON DALAM BAWANG TIWAI ( Eleutherine americana (Aubl.) Merr. ex K. Heyne.) DENGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI - Gunadi Tanusondjaja, Samuel
Eleutherine americana (Aubl.) Merr. ex K. Heyne is one of the plants which had been utilized by the local people in Indonesia, primarily in Borneo Island. In the plant, anthraquinone residue could be found as a result of pesticide usage. Although anthraquinone has the activity of antifungi and antimicrobial, it was also found to be carcinogenic. This research’s goal was to develop a method to determine the content of anthraquinone in the ethanol extract, n-hexane fraction, and ethyl acetate fraction of Eleutherine Americana (Aubl.) Merr. ex K. Heyne using High Performance Liquid Chromatography. The research commenced by optimation of the mobile phase which would be used in the subsequent processes, system suitability test and system validation which includes accuracy, precision, linearity, selectivity, and determination of the limit of detection and limit of quantification. Anthraquinone content in the plant was then determined by using of the mentioned method. The optimal mobile phase which would be used was acetonitrile-bidistilled water (1:1) with the flow rate of 1.25 mL/minute. Validation process result showed that the linearity was determined using correlation coefficient (r) of 0.9995 and determination coefficient (r2 ) of 0.9991 respectively. The limit of detection and limit of quantification value were 0.178 µg/mL and 0.594 µg/mL. In the intraday and interday precision tests, the results of the coefficient of variance for the reference were 0.627 and 0.774, while for the sample the results were 2.966 and 2.658. Recovery rates for the accuracy determination of the reference were between 98.976–101.452 % and for the sample, the results were 89.191–94.667 %. In the determination of the sample contents, anthraquinone was not detected in the water fraction and n-hexane fraction of Eleutherine americana (Aubl.) Merr. ex K. Heyne and it was detected in the ethanol extract of Eleutherine americana (Aubl.) Merr. ex K. Heyne, but it was not separated completely. The average anthraquinone content in the ethyl acetate fraction of Eleutherine americana (Aubl.) Merr. ex K. Heyne was 9.799 ± 5.243 µg/g.